Extreme precipitation associated with atmospheric rivers over West Antarctic ice shelves: insights from kilometre-scale regional climate modelling - E. Gilbert; D. Pishniak; J. A. Torres; A. Orr; M. Maclennan; M. Maclennan; N. Wever; K. Verro; K. Verro (The Cryosphere)
We explore how atmospheric rivers (ARs) in a summer and winter case interact with the topography of the Amundsen Sea Embayment, West Antarctica, and deposit significant precipitation amounts. To do this we use results from three regional climate models (RCMs: MetUM, Polar-WRF, HCLIM) at a spatial resolution of 1 km. Estimates of snowfall associated with both events from all three RCM simulations compare well against observed snow height measurements over the Thwaites and Pine Island ice shelves. By contrast, snowfall estimates from ERA5 reanalysis for both events are severely underestimated (by 3–4 times) compared to the measurements. Outputs from the RCMs also show that the ARs may be associated with several millimetres of rain in both the summer and winter cases, although in the absence of in situ measurements of rainfall, this result cannot be directly verified. The RCM simulations suggest that rainfall during these events can fall directly as supercooled drizzle but also that rainfall is concentrated around steep terrain due to the interaction of ARs with complex orography. We also show that while the amount of MetUM-simulated snowfall was comparatively resolution-insensitive, the amount of rainfall simulated was not, with rainfall amounts over Thwaites Ice Shelf 4–16 times higher in 1 km simulations compared to 12 km simulations. Our work highlights that kilometre-scale models are useful tools to investigate the total precipitation amount and its partitioning into rain and snow over this globally important and climatically sensitive region, and it highlights the critical need for in situ observations of rainfall.